2017
DOI: 10.4236/odem.2017.52005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Poisoning among Farmers by Chlorpyrifos: Case Report from Gaza Strip

Abstract: Spraying of organophosphorus insecticides (OPI) using high volume technique may result in poisoning cases among farmers or inhabitants in the spraying zone. This study reported a case among farmers in Gaza Strip, Palestine and discussed the follow up treatments. Results showed sever fasciculation of tongue and all muscle, pinpoint pupils not reacting to light, losing consciousness and disoriented, irritability, followed by diarrhea, vomiting, and severe inhibition of acetyl choline esterase (ACHE). Irritabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Our results agree with Yuzurihara et al [38], who found elevated liver enzymes (ALT and AST) in 16 patients had bilirubin measurements above 3 mg/dl. Similar results were found with acute poisoning [39,40]. The elevation of liver enzymes indicates oxidative stress in the liver of the neonates.…”
Section: Discussionsupporting
confidence: 82%
“…Our results agree with Yuzurihara et al [38], who found elevated liver enzymes (ALT and AST) in 16 patients had bilirubin measurements above 3 mg/dl. Similar results were found with acute poisoning [39,40]. The elevation of liver enzymes indicates oxidative stress in the liver of the neonates.…”
Section: Discussionsupporting
confidence: 82%
“…These symptoms are similar to organophosphate or carbamate poisoning among the population. These observations are in accordance with previously published work of poisoning cases among populations and farmers [17][18][19][20][21]. Furthermore, an immunity loss syndrome may also result from intensive chemotherapy [22].…”
Section: Consequences Of Chemotherapysupporting
confidence: 92%
“…Pesticides are widely used to control pests that affect agricultural crops and pests in homes, yards and gardens. Potential risks associated with pesticides includes groundwater contamination [2]- [11], risk to atmospheric contamination [12] [13], food contamination [14]- [20], soil contamination [21] [22] [23] [24] [25] health risks [26]- [31] risk to fish [32] [33] [34] [35] risk to cyanobacteria [36] [37] [38]. The above mentioned reports have a major focal point on herbicides since they are directly applied to the soil and being irrigated with water to be distributed in the top 15 cm of soil layer, the active layer for weed control.…”
Section: Introductionmentioning
confidence: 99%